Recuperação de urânio e de terras raras do resíduo gerado no tratamento de águas ácidas - Lima, Paulo (2014)
In some mines, where sulfide minerals can occur in form of pyrite, acid mine drainage may occur (AMD), as it constitutes one of the main environmental impact problems. To prevent the AMD to compromise aquifers compartments and reach the mine surroundings, a treatment consisting in its neutralization with the use of a hydrated lime suspension is conducted. Contaminants that were soluble in the AMD are precipitated, remaining through their solid phase. The work here presented aims at the recovery of uranium and rare earths found in one of these precipitates, which consists of calcium diuranate (DUCA, in reference to the uranium compound) and metal hydroxides in a calcium sulfate matrix. This material contains approximately 0.25% of triuranium octoxide (U3O8) and 2.5% of rare earth oxides (TR2O3). The recovery of uranium and rare earths contained in the precipitate was performed through a hydrometallurgical process involving steps of sulfuric leaching, solvent extraction and precipitation. From the stored DUCA mass, a recovery of approximately 12 tons/year of U3O8 in the form of concentrate, ammonium diuranate (NH4U2O7) and 120 tons/year of TR2O3 in the concentrate form of rare earths hydroxide (TR(OH)3) is expected. Test results of leaching with sulfuric acid presented solubilization of 96% for uranium and 90% for rare earths. Alamina 336 was used for uranium extraction from lixiviation and Alamina Primene for the rare earths. For re-extraction of uranium and rare earths, solutions of sodium chloride and hydrochloric acid were used respectively. A percentage yield of 99.7% and 99.9% was obtained in the steps of uranium extraction and re-extraction from lixiviation, respectively. The precipitation yield of uranium was 99.9%. On the extraction of rare earths a yield percentage of 99.9% was obtained for Ce, 99.7% for La and 92.0% for Nd. The obtained uranium and rare earths precipitates presented purities of 85.7% (U3O8) and 57.53% (TR), respectively. This work will serve as support to the decisions made by the Brazilian Nuclear Industries (INB) over the environmental remediation activities of the mine open pit.